Need Analysis of CTL-Based English-Speaking Material for the Chemistry Industry Students - Nila Swandari; Nur Mukminatien; Ekaning Dewanti Laksmi (Didaktika: Jurnal Kependidikan, 2024)
Proficiency in English is a requirement in today's industry. Adequate preparation of students for future workplace communication necessitates accurate planning and development of English-speaking materials. The process of conducting a need assessment is crucial in developing educational materials. This study aims to identify the requirements of students in the chemistry industry department at a vocational high school in Malang, Indonesia. This research serves as a foundation for creating speaking materials tailored to meet the industry's specific requirements. This study employs a qualitative methodology intending to acquire thorough data. Using questionnaires and interviews, data was gathered from a sample of 125 students, one English teacher, one chemistry industry teacher, and one professional chemistry industry worker. The results indicate that most students possess sufficient English proficiency, while only 12.50% achieved an outstanding level of proficiency. The teaching method employed is Contextual Teaching and Learning (CTL), while the assessment method is performance-based. The suggested materials for the chemistry industry topic are also provided, along with an evaluation of the current class.